TESTING THE J-CURVE PHENOMENON ON INDONESIA'S TRADE BALANCE WITH THE FIVE BIGGEST TRADING PARTNERS - Hamid, Muhammad Celvin; Tiara Nirmala; Imam Awaluddin (Journal of Management and Islamic Finance, 2024)
The J-Curve is an assumption that exchange rate depreciation will improve a country's trade balance in the long term. This phenomenon occurs when exchange rate depreciation causes the trade balance to worsen in the short term. However, in the long term the trade balance will improve and increase permanently. This study aims to test whether the J-Curve phenomenon occurs in Indonesia's bilateral trade balance with the five largest trading partners using the Vector Autoregressive (VAR) method and in the observation period 2010.1-2022.12. The results of the analysis of the Impulse Response Function (IRF) show that the J-Curve phenomenon occurs in the trade balance model between Indonesia and Japan and the United States. Meanwhile, for Indonesia's trade balance with the European Union, exchange rate depreciation can improve the trade balance directly. For Indonesia's trade balance with China and Singapore, exchange rate depreciation improves the trade balance initially, but will worsen (inverted J-curve) in the long term so that the long-term impact of exchange rate depreciation on the trade balance is negative.